The Influence of Brand Image, Product Quality, and Promotion on the Purchase Decision of Enis Glow Skincare in Tumenggungan Lamongan Village - Nur Himmatul Aliyah; Muhamad Imam Syairozi; Abid Muhtarom (Sean Institute, 2024)
The existence of this study aims to determine the influence of brand image, product quality, and promotion on the purchase decision of enis glow skincare in Tumenggungan Village, Lamongan. The sampling technique used was simple random sampling with a sample of 92 respondents. This study uses a quantitative method with a survey approach. The results of this study show that brand image does not have a significant effect on purchase decisions with a t-value of 1.789 < a table of 1.986. Product quality has a significant influence with a t-value of 4.202 > t table 1.986 and promotion has a significant influence with a t-value of 4.417 > t table 1.986.